A common insertion/deletion polymorphism of the thymidylate synthase (TYMS) gene is a determinant of red blood cell folate and homocysteine concentrations - MCPARTLIN, JOSEPH; SCOTT, JOHN MARTIN (Springer, 2005)
Substantial evidence suggests that a low folate/high homocysteine phenotype is pathogenic. We analyzed the impact of the thymidylate synthase (TYMS) 3UTR ins/del polymorphism on folate and homocysteine levels and assessed the relationship between the TYMS 3UTR ins/del polymorphism and key genetic and lifestyle variables. Among non-smokers only, the TYMS 3UTR ins/del polymorphism was significantly associated with red blood cell folate (RBC folate; P=0.002) and homocysteine (P=0.03) concentrations. Median RBC folate concentration was much higher for TYMS 3UTR del/del subjects (434 g/l) compared with either ins/ins (282 g/l) or ins/del (298 g/l) subjects. The median homocysteine concentration for del/del homozygotes was considerably lower compared with either ins/ins homozygotes or ins/del heterozygotes. A possible additive effect for the impact of the TYMS 3UTR del/del and MTHFR 677CC genotypes on RBC folate concentration was also observed. Our findings suggest that the TYMS 3UTR del/del genotype is a significant determinant of elevated RBC folate concentration in a non-smoking population of northwestern European adults and that this genotype confers protection against diseases for which a low folate/high homocysteine phenotype appears to be an etiologic component.
PUBLISHED
Keywords: Clinical Medicine